Editorial - Bronwyn Fredericks; Martin Nakata; Katelyn Barney (The Australian Journal of Indigenous Education, 2025)
We are pleased to bring you Volume 54 Issue 1 of The Australian Journal of Indigenous Education. We wish to thank the authors, reviewers, and editorial board members for their contributions to this volume. Thanks also to the Indigenous Engagement Division at The University of Queensland for their financial support of the journal. We hope you enjoy this volume of AJIE.